Abnormal body composition is a predictor of adverse outcomes after autologous haematopoietic cell transplantation. Issue 4 (25th March 2020) - Armenian, Saro H.; Iukuridze, Aleksi; Teh, Jennifer Berano; Mascarenhas, Kristen; Herrera, Alex; McCune, Jeannine S.; Zain, Jasmine M.; Mostoufi‐Moab, Sogol; McCormack, Shana; Slavin, Thomas P.; Scott, Jessica M.; Jones, Lee W.; et al.
Abstract: Background: The number of patients undergoing autologous haematopoietic cell transplant (HCT) is growing, but little is known about the factors that predict adverse outcomes. Low muscle mass and obesity are associated with disability and premature mortality in individuals with non‐malignant diseases and may predict outcomes after autologous HCT. Methods: This was a retrospective cohort study of 320 patients who underwent autologous HCT for Hodgkin or non‐Hodgkin lymphoma between 2009 and 2014. Sarcopenia {skeletal muscle index male: <43 cm/m 2 [body mass index (BMI) < 25 kg/m 2 ] or < 53 cm/m 2 [BMI ≥ 25 kg/m 2 ] and female: <41 cm/m 2 [regardless of BMI]) and obesity [total abdominal adiposity ≥450.0 cm 2 (male), ≥396.4 cm 2 (female)] were assessed from single‐slice abdominal pre‐HCT computed tomography images. Length of hospital stay, first unplanned intensive care unit admission, and 30‐day unplanned readmission were evaluated based on body composition using multivariable regression analysis, and mortality was evaluated with Kaplan–Meier analysis and Gray's test. Results: Median age at HCT was 53.3 years (range, 18.5 to 78.1 years); 26.3% were sarcopenic and an additional 7.8% were sarcopenic obese pre‐HCT. Sarcopenic obesity was associated with increased risk of prolonged hospitalization [odds ratio (OR) = 3.6, 95% confidence interval (CI) 1.3–9.8], intensive care unit admission (OR = 4.7, 95% CI 1.5–16.1), and unplanned readmission after HCT (OR = 13.6, 95% CI 2.5–62.8). Patients who were sarcopenic obese also had the highest mortality risk at 1 year [hazard ratio (HR): 3.9, 95% CI 1.1–11.0] and 5 years (HR: 2.5, 95% CI 1.1–5.5), compared with patients with normal body composition. Sarcopenia alone, but not obesity alone, was associated with an increased risk of these outcomes, albeit with a lower magnitude of risk than in patients who were sarcopenic obese. Conclusions: Sarcopenic obesity was an important predictor of outcomes in patients undergoing autologous HCT. These findings could inform targeted prevention strategies in patients at highest risk of complications after HCT.